Hands-on smart contract development with Solidity and Ethereum : from fundamentals to deployment - Solorio, Kevin; Kanna, Randall; Hoover, Dave H. (O'Reilly Media, 2019)
"Ready to dive into smart contract development for the blockchain? With this practical guide, experienced engineers and beginners alike will quickly learn the entire process for building smart contracts for Ethereum--the open source blockchain-based distributed computing platform. You'll get up to speed with the fundamentals and quickly move into builder mode. Kevin Solorio, Randall Kanna, and Dave Hoover show you how to create and test your own smart contract, create a frontend for users to interact with, and more. It's the perfect resource for people who want to break into the smart contract field but don't know where to start."--Page 4 of cover